How older adults recovering from substance use problems experience mattering - Nina Kavita Heggen Bahl; Hilde Eileen Nafstad; Rolv Mikkel Blakar; Emil Øversveen; Morten Brodahl; Ottar Ness; Isaac Prilleltensky (BMC, 2023)
Abstract Aim Mattering (to feel valued and add value to self and others) is a fundamental human experience and mechanism in recovery. In this paper, we concern ourselves with the recovery of older adults with substance problems. This population is on the rise in many Western countries. To offer mattering enhancing programs for this group, more knowledge about later life mattering in service-assisted recovery processes is needed. This study aims to explore experiences of mattering in older adults receiving services to recover from substance use problems. Methods A collaborative and deductive reflexive thematic approach was applied in analysing 23 interviews with participants using substance use services. Participants were recovering from different substance use problems: alcohol, medication and illegal substances. The participants were recruited from three different Norwegian social contexts: two urban and one medium size municipality. The age of the sample ranged from 65-80 years, with approximately equal numbers for those aged 60-69 (12 participants) and 70-80 (11 participants). Seven participants were women and 16 men. Results Three main themes were identified in the analysis: "relational experiences of mattering and not mattering", "service-related experiences of mattering and not mattering" and "recovery and psychological sense of community as interrelated phenomena to experiences of mattering". The findings illustrate various nuanced experiences of mattering and not mattering in later life recovery processes. Conclusions Overall, the participants' mattering experiences rested on fair, healthy and positive community relationships and fair and attentive services, where participants could feel valued and also have a chance to add value to others. Experiences of not mattering were precipitated by lack of support, disrespect, devaluation and loss of relationships, and also by being ignored and not receiving fair treatment and help by professionals. Importantly, reciprocal and enhancing relations between mattering, recovery and relational PSOC seem to exist and to be significant for the older adults' access to substance use services. Several practical implications are suggested to promote the therapeutic and preventive potentials of later life mattering in recovery.